The effect of the kaolinitic clay and asphaltenes on the rheological properties of Trinidad Lake Asphalt and Trinidad Petroleum Bitumen-clay composites / Rean Maharaj - Maharaj, Rean (2023)
Trinidad Lake Asphalt (TLA) is a source of superior quality asphalt and is often specified as a mandatory ingredient for paving in high-demand applications. The TLA resource is limited and expensive and the ability to synthetically convert refinery petroleum bitumen such as Trinidad Petroleum Bitumen (TPB) into a TLA-like material would be a very profitable and more sustainable approach. The objective of this paper is to determine whether kaolinitic clay and asphaltenes when blended with TPB can improve its rheological properties and produce a TLA-like material. Studies were conducted using dynamic (oscillatory) shear rheology (DSR) to measure changes on the rheological properties of complex modulus, G* (degree of stiffness) and phase angle, δ (degree of elasticity) of blends. Although the addition of kaolinite to TPB resulted in changes to the rheological properties (G* and δ) of the blends to values closer in magnitude to TLA, the properties of TLA were not achieved. Removal of the inorganic kaolinitic component from TLA resulted in a significant decrease in the complex modulus and an increase in the phase angle to values close to TPB (δ = 89.6 for TLA and δ = 89.1), demonstrating the key role played by the kaolinitic clay in the rheological properties of TLA.